(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2020)
The intensity of vascular streak dieback (VSD) disease is one of the major causes of decreased fine flavor cocoa production in Indonesia; therefore, it is essential to develop superior planting materials resistant to this disease. The purpose of the study was to conduct initial identification of yield potential and resistance level to VSD disease in several promising clones of fine flavor cocoa and to identify bean quality profile. This study was conducted at Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute, Jember, Indonesia, with an altitude of 45 m above sea level (asl.) and C climate type, according to the Schmidt-Ferguson classification system. The study design used a complete randomized block design consisting of 13 promising clones and 3 superior clones of fine flavor cocoa as control. Each treatment was repeated 4 times in blocks, and each plot consisted of 5 plants. The results showed that PNT 16 was potential to be developed as a superior promising clone of fine flavor cocoa with high yield potential (66.6 pods/ tree/year equal to 2.52 kg dry bean/tree/year) and low VSD level (VSD score: 0.4) in first year of production (4 years old after planting). The superior promising clone of PNT 16 comprises of 35.1 beans per pod with good quality, weighed by 1.25 g/bean, and a higher percentage of white seeds above 80% (94.9%). Furthermore, the specifications of the main flavor attributes are similar to ICCRI 09 and dominated by the browned roasted, nutty and browned fruit aroma. Therefore, the clone has the potential to be developed as one of the special cocoa products.